Fuzzy time series markov chain and discrete-time markov chain analysis of export gonggong in Batam - Anggraeni, Andini Setyo; Sabarinsyah, Sabarinsyah; Hayati, Nahrul; Wati, Dia Cahya; Ananda, Serly Tri (Universitas Islam Negeri Raden Intan Lampung, 2025)
Gonggong snails are an important fisheries commodity that has high economic value. However, freight on board export Gonggong has a bigger probability to decrease (below the half-term weighted average). So, more in-depth research is needed about Gonggong exports. In this research we will model and forecast Gonggong exports in Batam City using the Fuzzy Time Series Markov Chain (FTMC) and Discrete-Time Markov Chain (DTMC) methods. In FTMC the data will be divided into six states based on the fuzzification results, while in DTMC the data will be divided into four states, namely very low, low, high, and very high. Gonggong export data in kilograms for Batam City for 2020-2024 is sorted based on H.S. Code. The results of research using FTMC and DTMC provide similar results, namely that in the next six months, in December 2024, Gonggong's export size will experience an equilibrium condition where in the following months the export size will not experience significant changes. The highest possibility that will occur in this condition is that Gonggong's exports will be low with a probability of 39.99%, and the probability that exports will be very low is 24.75%. This is confirmed by the results of analysis using the fuzzy time series Markov chain. The results of the analysis predict that Gonggong's export in the following month, namely July 2024, will be 6,169.97 kg, which is in the low export size category. Predictions for the next month can also be made by continuing the calculation using FTMC.